Comparative phytochemical analysis, antioxidant and anti-inflammatory activities of rhizome and leaves of Curcuma caesia Roxb. and Curcuma longa L. - Charaya, Natasha; Choudhary, Priyvart; Prasad, Bobby; Bhawna; Sharma, Rohit; Kumar, Nishant; Singh, Gurmeet; Sharma, Nishesh (Plant Science Today, 2024)
Turmeric is a well-known medicinal herb used for traditional and medicinal purposes since ancient times. It is also an important ingredient in the cosmetic, food and pharmaceutical industries. Two common species, Curcuma longa L. (yellow turmeric) and Curcuma caesia Roxb. (black turmeric), are noted for their medicinal potential. However, commercially, yellow turmeric is more extensively explored than black turmeric. In the present study, a comparative phytochemical analysis was conducted, along with in vitro anti-inflammatory and antioxidant activity assessment of the rhizome and leaves of both yellow and black turmeric. GC-MS and FTIR analysis revealed a wide range of phytocompounds with known medicinal properties in both yellow and black turmeric rhizome. The presence of biologically significant phytocompounds such as methyl stearate, glycidyl oleate, curcumenol and eucalyptol in higher proportion in the rhizome of C. caseia compared to yellow turmeric supports further exploration of the commercial and medicinal potential of C. caseia. Antioxidant and anti-inflammatory analyses indicated that the rhizome of C. caseia possesses anti-inflammatory and antioxidant activities comparable to those of C. longa. This study also reports the presence of bioactive metabolites in the leaves of both black and yellow turmeric, along with anti-inflammatory and antioxidant activities in the leaves comparable to their respective rhizomes. These findings suggest that turmeric leaves could be as significant as turmeric rhizomes for medicinal and industrial applications.